Chemical processing of ceramics. - Lee, Burtrand Insung; Komarneni, Sridhar (Materials engineering (Taylor & Francis) ;, 2005)
The 27 contributions in this graduate textbook describe the synthesis and characterization of ceramic powders, the shaping of ceramic components via the sol-gel technique, and the fabrication of non-oxide ceramics. The final section walks through the more specialized processing of photonic crystals, high-temperature superconductors, ceramic membran.